Enhancing thermoelectric performance of Bi2Te3-based nanostructures through rational structure design. Issue 16 (6th April 2016) - Hong, Min; Chen, Zhi-Gang; Yang, Lei; Zou, Jin
Abstract : Enhanced thermoelectric performance in Te/Bi2 Te3 hierarchical nanostructures caused by strengthened phonon scattering, an optimized Fermi level, and suppressed bipolar conduction. Abstract : Nanostructuring has been successfully employed to enhance the thermoelectric performance of Bi2 Te3 due to its obtained low thermal conductivity. In order to further reduce the thermal conductivity, we designed a hierarchical nanostructure assembled with well-aligned Bi2 Te3 nanoplates using Te nanotubes as templates by a facile microwave-assisted solvothermal synthesis. From the comparisons of their thermoelectric performance and theoretical calculations with simple Bi2 Te3 nanostructures, we found that Te/Bi2 Te3 hierarchical nanostructures exhibit a higher figure-of-merit due to the optimized reduced Fermi level and enhanced phonon scattering, as well as the suppressed bipolar conduction. This study provides an effective approach to enhance the thermoelectric performance of Bi2 Te3 -based nanostructures by rationally designing the nanostructures.